Problems of Implementing Business Education in Early Childhood Education (PAUD): Systematic Literature Review (SLR) - Salsaufy Brilliant Nadila; Reza Dwi Prayitno; Aniek Indrawati; Ludi Vishnu Wardana; Angga Martha Mahendra (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Efforts to Increase Child Entrepreneurship in PAUD/TK institutions. Everyone needs to have an entrepreneurial spirit, including children at an early age. Entrepreneurship education is not just about educating prospective entrepreneurs or teaching children how to make money from an early age, but also about growing and developing the character that already exists in children. The purpose of this study was to: find out whether there are changes in children's habits and attitudes after doing fun activities in farming and increasing entrepreneurial spirit from an early age. This research uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to the word key. Based on the literature study conducted, it was found that the importance of planting and increasing understanding of the concept of entrepreneurship from an early age starting from early childhood education, this implementation needs examples in the form of activities carried out by playing to provide a good understanding of students. Another problem, students are less motivated to look for reference materials related to the material provided. Based on the analysis of learning tools, the entrepreneurship material being taught is still not sustainable so that the expected competencies are not clear. In addition, learning activities are still centered on the teacher. The results of the analysis of reference books to see the contents of the material, especially the main economic activity material. Instilling an entrepreneurial spirit from an early age makes children have a strong business spirit, sense of responsibility and independence. Efforts to Increase Child Entrepreneurship in PAUD/TK institutions. Everyone needs to have an entrepreneurial spirit, including children at an early age. Entrepreneurship education is not just about educating prospective entrepreneurs or teaching children how to make money from an early age, but also about growing and developing the character that already exists in children. The purpose of this study was to: find out whether there are changes in children's habits and attitudes after doing fun activities in farming and increasing entrepreneurial spirit from an early age. This research uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to the word key. Based on the literature study conducted, it was found that the importance of planting and increasing understanding of the concept of entrepreneurship from an early age starting from early childhood education, this implementation needs examples in the form of activities carried out by playing to provide a good understanding of students. Another problem, students are less motivated to look for reference materials related to the material provided. Based on the analysis of learning tools, the entrepreneurship material being taught is still not sustainable so that the expected competencies are not clear. In addition, learning activities are still centered on the teacher. The results of the analysis of reference books to see the contents of the material, especially the main economic activity material. Instilling an entrepreneurial spirit from an early age makes children have a strong business spirit, sense of responsibility and independence.